PELATIHAN OPTIMALISASI CITRA CT UROGRAFI DENGAN MEDIA KONTRAS POSITIF DAN MEDIA KONTRAS NEGATIF - Widya Mufida; Muhamad Faik; Ahmad Faesol (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2023)
CT Scan Urography is an examination using positive contrast media. Several three-dimensional reconstruction software applications found in CT Scan modalities include nerve marking, autobone, CT perfusion, smartcore, bone mineral densitometry, noise and artifact correction, denta scan, CT dose profile, multi planar volume rendering, maximum intensity projection, volume rendering, shaded surface display, multi planar reconstruction and tracking. Community service activities aim to improve soft skills and add insight to radiographers, alumni of the UNISA D3 Radiology Study Program and Radiology D3 Study Program students by training and simulating CT Scan Urography image processing. Optimal image processing in CT Scan examinations can minimize the occurrence of repetition so as to limit the radiation dose received by the patient so that it is necessary to increase the soft skills of the radiographer by means of training and simulation of CT Scan Urography image processing.